The Geometric Design of Horizontal Alignment: A Case of Serpong – Balaraja Toll Road, Indonesia - Rifany Rizki Salsabila; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
Rapid economic growth and a significant population necessitate efficient road functioning to facilitate community needs in terms of time, costs, income, health, comfort, and safety. Geometric road design serves as the cornerstone of road safety considerations and places significant emphasis on the strategic placement of symmetrical physical road components. This research is about planning the geometric design of the Serpong - Balaraja toll road, especially the horizontal alignment and this aims to know the planning of the toll road, the research conducted on Serpong – Balaraja Toll Road, located in Tangerang Regency in South Tangerang City. The road starts from STA 0+000 to 5+150. This study employs a measurable approach, where the data collected is derived mathematically using established formulas. The data utilized consists of primary data, specifically situation maps, road traffic information, and topographical details extracted from Google Earth. The results of the planning showed that there are four bends in this road. The first and the fourth bend is full circle type with a radius of 850 m; the curved length (Lc) for the first bend is 86.37 m, and the second bend is 45.994 m. Second is the spiral-spiral (SS) type, with a 160 m radius and a curved length (Ls) of 122.690 m. third is the spiral-circle-spiral (SCS) type with a 350 m radius, with a curved length (Ls) of 40 m. The calculation of this planning bases on road geometric design guidelines 2021.